Kemandirian Belajar Ditinjau Dari KreatifitasBelajar Dan Intensitas Pemanfaatan Perpustakaan Pada Siswa Kelas X Akuntansi Mata Pelajaran Ips Di Smk N 1 Klaten - Fitriana, Niken Dyah Ayu; , Djalal Fuadi, MM (2017)
The purpose of this study are : 1) C reativity effect of learning on student learning independence class X Accounting SMK N 1 Klaten. 2) T he influence of the intensity of use ofnthe library to the independence of student learning class X Accounting SMK N 1 Klaten. 3) I nfluence learning creativity and intensity of use 2 of the library to the independence of student learning class X Accounting SMK N 1 Klaten. This study uses quantitative methods associative. The population in this study were all students of class X accounting SMK N 1 Klaten. The sampling technique used Proporsional Sam ple random Sampling that as many as 143 respondents. Necessary dataobtained through questionnaires and documentation. The questionnai re has previously been tested an d tested for validity and reliability were tested. Data analysis technique used is the prer equisite analysis using normality test and linearity test, whereas hypothesis testing using multiple linear regression, F test, t - test, R2, and the relative contribution and effective. The results of the regression equation obtained regression independent learning that Y = 14,085 + 0,346X 1 + 0,452X 2 . The conclusion of this study were: 1) Learning creativity significant effect on student learning independence. This is evident from the test result were obtained t t hitung > t tabel (5,080 > 1,985); 2) Intensity of use the library significant incluence the independence student learning. This is evident from the test result were obtained t t hitung > t tabel (6,674 > 1,985); 3) Creativity and intensisty of use of the library studying together significant effect on s tudent learning independence. This isevident from the test resut were obtained F F hitung > F tabel (52,156 > 3,090). Coefficient determination test result obtained R 2 = 0,518, meaning that 51,8% mean change / variation Y (Independent Learning) caused by the change / variation of the variable X ( Learning Creativity and Intensity of Library Use), while 48,2% the rest is to changes in other variables not included in other models and so forth. Keywords: independent learning, learning creativity, the i ntensit y of the u se of l ibra ries